Contributions to a theoretical research in the field of communication. What is Library / Documentation / Information Science? - López Yepes, José (2022)
This paper discusses the concept of Information Science / Library Science / Documentation in the light of the present-day terminological problem that affects them. The scope of such a crisis go beyond mere epistemological aspects and include issues related to training, the labor market, university admissions, etc. We argue for an understanding of the above concept as science for science and information science in the context of Communication.